The Contribution of Zapin as One of Malay Traditional Arts in Curriculum 2013 - Roza, Ellya; Zulkifli, Nur Aisyah (AT-TALIM, 2017)
Zapin consists of three elements which are complementary to create movement harmony and rhythm that beautiful to look, heard and seen. They are music, song and dance. Zapin is one culture comes from Arab that developed in archipelago line with Islamization process. Zapin in Nusantara grew and developed in accordance with the customs and conditions of the local community. It becomes palace art for events such as welcoming guests and celebrations in the kingdom and also entertainment for society. The study aims to determine the contribution of Zapin in the Curricullum 2013. A Mixed research was used where the data taken from documentation, observation, and interview. The finding of the study showed that although modern art has been rife enter and expand in the archipelago but Zapin as cultural heritage still exist in society because of its content in accordance with teaching point and attitude of society that moral and spiritual precedence. It means that Zapin with all devices containing a core competence value contained in curriculum 2013. It is concluded that the contribution of Zapin as one of Malay traditional arts might contribute to the strengthening of curriculum 2013.